Factors associated with medical students' psychological wellbeing, coping and personality, as well as wellbeing support: A quantitative and qualitative exploration - Hawsawi, Aisha (2024)
Background In recent years, there has been a notable shift in awareness towards the psychological wellbeing and mental health of healthcare professionals and students, emerging as a pressing public health concern with implications for the quality of care delivery. Healthcare professionals are confronted with numerous stressors in their daily roles, which can significantly impact their overall wellbeing. Particular emphasis has been placed on the mental health of medical students who, early on in their career path, have been documented to present with poor mental health levels that exceed those of the general student population worldwide and that have been attributed largely to the demanding nature of their studies; this challenge has been further exacerbated by the impacts of the COVID-19 pandemic. While research on the psychological wellbeing of medical students has been growing, much of the existing literature tends to concentrate on quantitative studies, which have primarily investigated the factors that negatively affect medical students' psychological wellbeing, often overlooking the potential positive influences on their academic and personal lives during their medical training. Hence, there is an identified need to adopt a more comprehensive approach that encompasses both positive and negative factors impacting medical students' psychological wellbeing in order to look into aspects that can promote wellbeing as well as ‘fix’ wellbeing issues; this necessitates a balanced exploration from both quantitative and qualitative perspectives in order to gain a deeper understanding into what determines the psychological wellbeing state of medical students. Furthermore, understanding medical students' utilisation of wellbeing support services is crucial. Despite existing wellbeing support resources, limited insight exists into students' acceptability of these resources and potential needs for tailored wellbeing support.